PERBEDAAN LATIHAN MENGGUNAKAN PELAMPUNG PULL BUOY DAN ROMPI TERHADAP KECEPATAN RENANG GAYA BEBAS 50 METER PADA ATLET TIRTA TUNGGAL SEMARANG (Indonesian Journal for Physical Education and Sport, 2021)
Initial observations found that exercise using buoys was better to improve the focus of hand-to-foot coordination. The purpose of the study was to find out the influence and test the exercise of pull buoys and vests on the speed of swimming. This type of research is a quantitative research pre-experimental design to find causal relationships dau faktor. The target of this study is all tirta tunggal semarang athletes. Data analysis techniques using description analysis, classic asusmsi test, hypothesis test. Results of the study; (1) The F-count value is 5,853>F-table 4,410, the signififsi is 0.030<0.05. It means Ho: rejected and Ha: accepted. There is an effect of pull buoy swimming exercises on swimmingspeed; (2) F-count value 7,808>F-table 4,410, signifkansi 0.032<0,05.artiya Ho: rejected and Ha: accepted. There is an effect of buoy vest swimming exercises on swimmingspeed; (3) The F-count value is 35,379>F-table 4,410, signifkansi 0.002<0,05.meaning Ho: rejected and Ha: accepted. Ada influence of pull buoy swimming exercises and vests on the swimming speed of athletes Tirta TunggalSemarang; (4) The pull buoy exercise against produces an R-Square value of 0.563, while the vest exercise produces an R-Square value of 0.367. It is concluded that the value of 0.563>0.367, then pull buoy exercises are better than using a vest. In conclusion, pull buoy exercises are better in meningkatkan swimming speed athlete Tirta Tunggal semarang. Advice, trainers and athletes can use pull buoy exercises as a form of exercise program at swimming speed.